Politique de l'eau au Québec : comment décentraliser sans faire de remous ? - Alexandre Brun; Frédéric Lasserre (Cybergeo)
In November 2002, the Quebec government decided to go ahead with a new water governance policy. It calls for the creation of Watershed Organisations (WO), local institutions responsible for the definition of Water Management Schemes. But these WOs lack their own funding and remain very dependent on the goodwill of the Quebec State. The latter may not, after the victory of the Liberals in 2003, wish to fully implement the new policy, for budgetary and for fear the WOs take too much power against the provincial government.